Transfer of Competencies to the Secretariat for the economy:Motu Proprio On the Transfer of the Ordinary Section of the Administration of the Patrimony of the Apostolic See to the Secretariat for the Economy - Franziskus Papst 1936- (2014)
In July 2014, Pope Francis issued a motu proprio on the transfer of the Ordinary Section of the Administration of the Patrimony of the Apostolic See to the Secretariat of the Economy.